Application of mesenchymal stem cells in corneal regeneration. (December 2021) - Ghiasi, Mohsen; Jadidi, Khosrow; Hashemi, Mehrdad; Zare, Hamed; Salimi, Ali; Aghamollaei, Hossein
Graphical abstract: Highlights: Mesenchymal Stem cell-based strategies have great potential in the regeneration of cornea. Detailed classification of the application of mesenchymal stem cells used in different layers of the cornea was presented. There are some challenges in using mesenchymal stem cells in corneal cell therapy. Abstract: Due to delicate its structure, the cornea is susceptible to physical, chemical, and genetic damages. Corneal transplantation is the main treatment for serious corneal damage, but it faces significant challenges, including donor shortages and severe complications. In recent years, cell therapy is suggested as a novel alternative method for corneal regeneration. Regarding the unique characteristics of Mesenchymal stem cells including the potential to differentiate into discrete cell types, secretion of growth factors, mobilization potency, and availability from different sources; special attention has been paid to these cells in corneal engineering. Differentiation of MSCs into specialized corneal cells such as keratocytes, epithelial and endothelial cells is reported. Potential for Treatment of keratitis, reducing inflammation, and inhibition of neovascularization by MSCs, introducing them as novel agents for corneal repairing. In this review, various types of MSCs used to treat corneal injuries as well as their potential for restoring different corneal layers was investigated.